Dimensi Kompetitif Lingkungan Rantai Pasokan Upaya Mencapai Keunggulan Bersaing UMKM di Malang - Sri Wahjuni Latifah; Uci Yuliati (Benefit: Jurnal Manajemen dan Bisnis, 2019)
Research on the competitive environment the supply chain dimension SMALL MEDIUM ENTERPRISES(SMEs) in Malang was conducted on forty (40) the SMEs engaged in the production of foods and beverages such as make tempe, to make fruit, candied fruit, dodol fruit, fruit syrup, bakery or processed foods such as frozen foods. The purpose of this study is to determine the competitive dimension factor of the environment to improve the performance of SMEs in Malang so that it can be used to achieve competitive advantage. Variable dimensions of internal environment include innovation, intelectual knowledge, best practice and internationalisation of economic policy. While the dimensions of the external environment consists of traditional rivalries, the newcomer, substitute products, the production costs of dam model of online marketing. SMEs a competitive advantage is excellence through deferensiasi products, consumer confidence towards products and consumer satisfaction towards products. Data were collected by quetionary, and interview to manager of SME, employees, consumer and management of association of SMEs. Data analysis Teqniquewith descriptive qualitative. Previously the data in the quality test through the validity test, reliability test and fit model test and Regression Analysis.The results showed that the dimensions of the internal environment has no effect against a competitive advantage and the dimensions of the external environment to a competitive advantage. While environmental factors are moderated by internal external environment affect the competitive advantage SMEsKeywors: Environmental dimension, SME, competitive advantage